2016
DOI: 10.1007/s00330-016-4427-y
|View full text |Cite
|
Sign up to set email alerts
|

Do quantitative and qualitative shear wave elastography have a role in evaluating musculoskeletal soft tissue masses?

Abstract: ObjectivesTo determine if quantitative and qualitative shear wave elastography have roles in evaluating musculoskeletal masses.Methods105 consecutive patients, prospectively referred for biopsy within a specialist sarcoma centre, underwent B-mode, quantitative (m/s) and qualitative (colour map) shear wave elastography. Reference was histology from subsequent biopsy or excision where possible. Statistical modelling was performed to test elastography data and/or B-mode imaging in predicting malignancy.ResultsOf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 23 publications
(24 reference statements)
6
33
2
Order By: Relevance
“…The authors concluded that although there may be some evidence of an association between lower shear-wave velocity and soft-tissue malignancy, particularly in the transverse plane, this did not result in a substantive improvement in the ability to detect malignancy over B-mode consensus classification (50). Another similar SWE study from the same institution on 50 soft-tissue tumors, 15 of which were malignant and 35 benign, showed more encouraging results.…”
Section: Swe Of Soft-tissue Musculoskeletal Massesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that although there may be some evidence of an association between lower shear-wave velocity and soft-tissue malignancy, particularly in the transverse plane, this did not result in a substantive improvement in the ability to detect malignancy over B-mode consensus classification (50). Another similar SWE study from the same institution on 50 soft-tissue tumors, 15 of which were malignant and 35 benign, showed more encouraging results.…”
Section: Swe Of Soft-tissue Musculoskeletal Massesmentioning
confidence: 99%
“…SWE also allowed characterization of thyroid nodules (with the majority of malignant lesions being stiffer than benign nodules [47]) and various benign and malignant liver lesions (48,49). To our knowledge, currently there are two studies on the utility of SWE in evaluation of musculoskeletal soft-tissue masses (50,51). In one, Pass and collaborators (50) conducted a Bmode and SWE study of 105 biopsy-proven musculoskeletal soft-tissue tumors, 39 of which were malignant and 66 benign.…”
Section: Swe Of Soft-tissue Musculoskeletal Massesmentioning
confidence: 99%
“…The technique provides a noninvasive, relatively inexpensive, quantitative measure of local tissue elasticity. To date, only a few feasibility studies have investigated its practical use in delineating benign versus malignant disease, so far showing mixed results [1][2][3][4]. Traditional (strain) elastography requires external compression to determine the mechanical properties of tissues [5].…”
Section: Introductionmentioning
confidence: 99%
“…almost perfect SWE repeatability in resting [13][14][15][16] and stretched [17,18] normal skeletal tissue. Multiple previous studies have investigated the diagnostic value of sonoelastography for soft tissue lesions [1,3,4,19,20]. Despite this, there is only limited published data on the reproducibility and repeatability of SWE and how it may be affected by tumour characteristics such as depth and location.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant lesions have been shown to be stiffer on strain elastography compared with benign lesions on a semi-quantitative scale, similar to lesions outside of the musculoskeletal system[50]. However, a recently published study by the group in Leeds assessing the role of shear wave elastography in musculoskeletal tumours has been unable to replicate these early findings, with the authors concluding that there is currently no additional role for shear wave elastography in soft tissue tumours compared with B mode imaging[51]. The authors found no statistically significant association between shear wave velocity and malignancy.…”
Section: Musculoskeletal Applications Of Elastographymentioning
confidence: 99%